The correlation between gear contact friction and ball on disc friction measurements. (March 2015) - Björling, M.; Miettinen, J.; Marklund, P.; Lehtovaara, A.; Larsson, R.
Abstract: Running experiments with full-size gearboxes from the actual application has the advantage of giving realistic results in terms of power losses. The drawback is extensive costs, lengthy testing, and the difficulty in differentiating between load dependent and load independent losses, and which losses are coming from the gears, seals, bearings or synchronizers. In this work, the correlation between friction measurements conducted in a ball-on-disc machine and friction measurements conducted in a back-to-back gear rig is investigated. The correlation between the gear tests and the ball-on-disc tests was reasonably good in terms of absolute values, and the shape of the friction curves was similar, indicating that the ball-on-disc measurements to a large extent are capturing the behavior of the gear contact. Abstract : Graphical abstract: Abstract : Highlights: Friction is measured with three oils in a gear test rig, and in a ball-on-disc rig. Test conditions in both rigs are as similar as possible. The ranking of the three oils is the same in both rigs at both temperatures. Ball-on-disc tests could be used as a cheaper alternative to gear tests. Friction mapping gives information of several arbitrary gears in one test.